FPGA-Based Implementation of an Underwater Quantum Key Distribution System With BB84 Protocol - Burak Kebapci; Vecdi Emre Levent; Sude Ergin; Gorkem Mutlu; Ibrahim Baglica; Anilcan Tosun; Pietro Paglierani; Konstantinos Pelekanakis; Roberto Petroccia; Joao Alves; Murat Uysal (IEEE Photonics Journal, 2023)
As threats in the maritime domain diversify, securing data transmission becomes critical for underwater wireless networks designed for the surveillance of critical infrastructure and maritime border protection. This has sparked interest in underwater Quantum Key Distribution (QKD). In this paper, we present an FPGA-based real-time implementation of an underwater QKD system based on the BB84 protocol. The QKD unit is built on a hybrid computation system consisting of an FPGA and an on-board computer (OBC) interfaced with optical front-ends. A real-time photon counting module is implemented on FPGA. The transmitter and receiver units are powered with external UPS and all system parameters can be monitored from the connected computers. The system is equipped with a visible laser and an alignment indicator to validate successful manual alignment. Secure key distribution at a rate of 100 qubits per second was successfully tested over a link distance of 7 meters.